Rancang Bangun dan Evaluasi Kinerja Irigasi Mikro di Pulau Haruku, Maluku - Dadan Rahmandani; Hanhan Ahmad Sofiyuddin; Ratna Adiana; Abid Hendri Indarta; Hayatuddin Tuasikal (Balai Teknik Irigasi, 2020)
The development of irrigated agricultural land on small islands faces many obstacles due to the very limited water availability. The development of irrigated land is often constrained by the relatively high need for water for agricultural land, resulting in competition with domestic water needs. Thus, the development of irrigated land needs to be carried out by applying water-efficient irrigation technologies such as micro irrigation. The research was conducted to test and identify the impact of applying micro irrigation technology on small islands. The research was conducted conditions in Haruku Island, Central Maluku through testing the application and measurement of network performance. The results of the application showed that network installation, irrigation operations, fertilization work, pest control and weeding on the application of micro irrigation were easier and faster. Conventional irrigation using watering pot requires a long time and a lot of labor to meet the water needs of plants. Thus, at the research location, water needs could not be fulfilled by nearly 47% of the period during the growing season and crop production was not optimal. Another case with micro irrigation where water can be given at the right volume and time. Soil moisture can be maintained at optimum levels through short irrigation intervals and of longer duration. From the socio-economic aspect, there is a good performance in the economic aspect of the farmers, which is shown by an increase in income and being able to set aside a portion of their income for savings. Meanwhile, from the social aspect, the application of micro irrigation technology is required by farmers on Haruku Island. These results indicate that micro irrigation could be an alternative technology to support the management of water resources in small islands, especially on Haruku Island.The development of irrigated agricultural land on small islands faces many obstacles due to the very limited water availability. The development of irrigated land is often constrained by the relatively high need for water for agricultural land, resulting in competition with domestic water needs. Thus, the development of irrigated land needs to be carried out by applying water-efficient irrigation technologies such as micro irrigation. The research was conducted to test and identify the impact of applying micro irrigation technology on small islands. The research was conducted conditions in Haruku Island, Central Maluku through testing the application and measurement of network performance. The results of the application showed that network installation, irrigation operations, fertilization work, pest control and weeding on the application of micro irrigation were easier and faster. Conventional irrigation using watering pot requires a long time and a lot of labor to meet the water needs of plants. Thus, at the research location, water needs could not be fulfilled by nearly 47% of the period during the growing season and crop production was not optimal. Another case with micro irrigation where water can be given at the right volume and time. Soil moisture can be maintained at optimum levels through short irrigation intervals and of longer duration. From the socio-economic aspect, there is a good performance in the economic aspect of the farmers, which is shown by an increase in income and being able to set aside a portion of their income for savings. Meanwhile, from the social aspect, the application of micro irrigation technology is required by farmers on Haruku Island. These results indicate that micro irrigation could be an alternative technology to support the management of water resources in small islands, especially on Haruku Island.